Curcumin attenuates cardiomyocyte hypertrophy induced by high glucose and insulin via the PPARγ/Akt/NO signaling pathway. Issue 2 (May 2015) - Chen, Rongchun; Peng, Xiaofeng; Du, Weimin; Wu, Yang; Huang, Bo; Xue, Lai; Wu, Qin; Qiu, Hongmei; Jiang, Qingsong
Highlights The mechanism of diabetic cardiomyopathy is still unclear. We made an in vitro diabetic cardiac hypertrophy model with HGI. We found PPARg/Akt/NO signal pathway was involved in diabetic cardiac hypertrophy. Curcumin attenuates cardiac hypertrophy induced by HGI via this pathway.